Comportamento de Orius insidiosus predando Aphis gossypii criados em variedades de algodão transgênico e convencional - Veiga, Ana Carolina Pires [UNESP]; De Laurentis, Valéria Lucas [UNESP]; Vacari, Alessandra Marieli [UNESP]; Volpe, Haroldo Xavier Linhares [UNESP]; Ramalho, Dagmara Gomes; De Bortoli, Sergio Antonio [UNESP] (Universidade Estadual de Maringa, 2014)
The objective of this study was to evaluate the functional response of Orius insidiosus preying on the third and fourth instars of Aphis gossypii nymphs that were reared on transgenic NuOPAL (Bollgard I Event 531) and conventional Buriti cotton varieties. Fifty O. insidiosus female bugs aged 12-24h were distributed into five different Petri dishes with different densities of A. gossypii (2, 4, 8, 16, and 32 nymphs per plate) for each cotton variety. The number of prey consumed was evaluated over the course of 12h, with a final assessment at 24h. The handling times (Th) and attack rates (a) were 0.0697h and 1.1862h-1, respectively, for the Buriti variety and 0.0713h and 0.3030h-1, respectively, for the NuOPAL variety. The average number of prey consumed by O. insidiosus was similar for both varieties at 24h and at higher densities; the attack rate was higher for the Buriti-reared aphid prey than for the NuOPAL-reared aphids.
Behavior of Orius insidiosus preying on Aphis gossypii reared on transgenic and conventional cotton varieties
Keywords: Cotton aphid; Functional response; Gossypium hirsutum; Minute pirate bug; Transgenic plants